USAGE OF COUNTABLE AND UNCOUNTABLE NOUNS IN ENGLISH (Лучшие интеллектуальные исследования, 2025)
Annotation: This research paper explores the significance and application of countable and uncountable nouns in the English language. Understanding these two categories is fundamental for constructing grammatically correct sentences and communicating effectively. This paper categorizes nouns into countable and uncountable, detailing their grammatical features, usage rules, and common challenges faced by learners. Through examples and analyses, this paper aims to enhance understanding of how these nouns function within the language.